METODOLOGIA DA RESOLUÇÃO DE PROBLEMAS E A CONSTRUÇÃO DO CONCEITO DE LIMITE EM UMA TURMA DO 3º ANO DO ENSINO MÉDIO - Pereira, Carolina Conrado (2015)
This study developed in the Professional Master's Degree in Physics and Mathematics Teaching of the Franciscan University Center aims to investigate if the Problem Solving methodology contributes to the understanding of the concept of real functions limit in students of the third grade of high school. The starting point was the finding that some textbooks, especially the high school books of the senior year, show in the final chapter, the introduction of concepts related to differential calculus, what is linked to the notion of functions limit of a real variable. Noticed this fact, we questioned why this content was not treated and included in Math‟s program of this level of education. The research was conducted with students of the third grade of high school from a public school in Santa Cruz do Sul (RS) and it used the qualitative research methodology and the teaching Problem Solving methodology with the theoretical assumptions of Tall and Vinner (1981), that deal with theories of "concept image" and "concept definition" for knowledge acquisition. In 10 meetings, each one with 50 minutes, we deal with notions of limit, the relation between epsilon and delta symbols, concept of lateral and infinite limits that were applied according to nine steps defined by the authors. The problems have been formulated to analyze if the construction of different conceptual images through the Problem Solving methodology would facilitate the understanding of the notion of limit. By means of this research, it can be concluded that the application of the Problem Solving methodology was valid, since it allowed students to build conceptual images to define the concept of limit. At the end of each meeting, we found that students have evolved knowledge about limit, by appropriating concepts that are taught only in Higher Education.